TECHNOLOGY OF EDUCATION OF PATRIOTIC QUALITIES OF STUDENTS OF PROFESSIONAL EDUCATIONAL INSTITUTIONS (American Journal of Interdisciplinary Research and Development, 2022)
In our country, socio-pedagogical mechanisms of spiritual and moral education of young people have been developed, and on the basis of them, great attention is paid to educating students as perfect people in all respects. Also, there is a need to interpret the training of professionals with an independent civic outlook, to develop such qualities as patriotism, steadfastness, and willfulness in them as a pedagogical phenomenon of urgent importance, and to create methodologies of practical description. In order to strengthen independence, build a free and prosperous Motherland, a free and prosperous life, the role of literature is extremely important in shaping the ideology of national independence in the minds of soldiers. Cultivating the thinking of students, expanding the scope of thinking is a high human virtue - our holy books "Avesta", "Holy Qur'an" are used to form a sense of patriotism. and wisdoms mentioned in "Hadiths", great royal works of Uzbek literature: "City of Virtuous People", "Boburnoma", "Tuziklari of Timur" were expressed. The heroic struggles of our national heroes such as Tomaris, Shiroq, Spitamen, J. Manguberdi, Temur Malik, Amir Temur for the fate of the country, that they were unparalleled heroes, even their enemies recognized their bravery, and that our country raised such incomparable heroes in an attractive way to the youth of today. delivery is required.